THE MATHEMATIC SUPPORT FOR SHOWING CONCEPT MODELS - Малярчук, В. О; Кононюк, А. Ю.; Малінкін, І. В. (Science-based technologies, 2014)
The structural diagram of the universal software, of the creation mathematical models of the concepts produced in raster devices, was provided. The software oriented on documentation release about the created mathematical model of concept that is a set of textual and graphic elements is described. The offered HTML- interface is considered from the set of subprograms of two groups. First of them are general-system that adjust system to particular devices and parameter points and second ones are subprograms that form elements of image of the model concepts: contours of arcs, circles, lines etc are registered for each symbol by subprogram (UNICODE).The structure of the raster interface was described together with algorithms forming a conceptual expression –based to work in real time. The syntax and semantics of the main body, array segments, solid circles, solid arcs, array of standard models of concepts, array text were described.